Postcolonial Prepositions:Semantics and Geopolitics in the Danosphere - Levisen, Carsten (2018)
This study explores Danish-Greenlandic relations from the vantage point of two salient Danish constructions: på Grønland ‘on Greenland’ and i Grønland ‘in Greenland’. The two prepositions i ‘in’ and på ‘on’ present two different construals of Greenland and/in the Danosphere. In Danish geopolitics these prepositions have come to stand for two different Danish attitudes towards Greenland, in short, the på-attitude and the i-attitude. In order to scrutinize this Danish “grammar of Greenland”, the paper makes use of Postcolonial Semantics, an NSM-based framework for understanding meaning and discourse in (post) colonial contexts (Levisen, in progress). The aim of the paper is to provide semantic explications for the på-construction and the i-construction, and to articulate the related på-attitudes and the i-attitudes by means of cultural scripts. The analysis draws heavily on Goddard’s work on the semantics of “on-constructions” in English (Goddard 2013), and takes up some of his ideas on how symbolic and indexical meaning can be studied together within the NSM-framework (see in particular Goddard 2002). Empirically, the study relies on discursive evidence from two Danish social media sites: Heste-Nettet ‘Horse Net’, and Pokernet ‘Poker Net’. While horses and poker have little to do with Greenland and (post)coloniality, both communities have recently taken up the question of “what preposition to use when talking about Greenland”. Rich on metapragmatic statements and emic viewpoints, these discussions provide a window on the values, indexicalities, and naïve pictures of the world that undergird the choice of preposition. The analysis shows that the på-attitude emphasizes Greenland’s “islandness” and by implication, its inability to become an independent nation, whereas the i-attitude allocates attention to Greenland’s status as a nation, and by implication, Denmark’s obligation to establish a truly postcolonial relation with a fully independent Greenlandic nation. It is demonstrated how NSM semantics can be used to ...